2010
DOI: 10.4061/2010/597098
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Ribonucleotide Reductase‐Antimetabolite Drug Interaction in Cancer Cell Lines

Abstract: RRM1 is a determinant of gemcitabine efficacy in cancer patients. However, the precision of predicting tumor response based on RRM1 levels is not optimal. We used gene-specific overexpression and RNA interference to assess RRM1's impact on different classes of cytotoxic agents, on drug-drug interactions, and the modulating impact of other molecular and cellular parameters. RRM1 was the dominant determinant of gemcitabine efficacy in various cancer cell lines. RRM1 also impacted the efficacy of other antime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…In fact, we have identified and reported at least three parameters that affect these interactions. 24,25 Finally, studies have suggested that the chosen reagent for in situ quantification of ERCC1 (monoclonal antibody 8F1) may detect other molecules of similar immunoreactivity and cellular localization than ERCC1, which may explain the observed lack of correlation in the current study. 26 We have previously reported a modest correlation (r ϭ 0.42) between RRM1 mRNA levels determined in fresh-frozen tumor specimens and in situ protein levels as determined by AQUA from specimens collected at a single institution.…”
Section: Discussioncontrasting
confidence: 51%
“…In fact, we have identified and reported at least three parameters that affect these interactions. 24,25 Finally, studies have suggested that the chosen reagent for in situ quantification of ERCC1 (monoclonal antibody 8F1) may detect other molecules of similar immunoreactivity and cellular localization than ERCC1, which may explain the observed lack of correlation in the current study. 26 We have previously reported a modest correlation (r ϭ 0.42) between RRM1 mRNA levels determined in fresh-frozen tumor specimens and in situ protein levels as determined by AQUA from specimens collected at a single institution.…”
Section: Discussioncontrasting
confidence: 51%
“…Reduction of RRM1 expression through RNA interference abrogated the induced gemcitabine resistance. 35 Ribonucleotide reductase enzymatic activity is modulated by levels of its M2 subunit. An over-expression of RRM2 is associated with resistance to gemcitabine and down regulation of RRM2 by siRNA enhanced gemcitabine cytotoxicity, both in vitro and in vivo in pancreatic adenocarcinoma.…”
Section: Resistancementioning
confidence: 99%
“…9,35 Therefore, it is possible that the attenuation of RRM1 expression using siRNA technology may also be beneficial to overcoming chemoresistance to those anticancer drugs as well.…”
Section: Methodsmentioning
confidence: 99%